Nicotinic receptor-associated modulation of stimulatory and inhibitory neurotransmitters in NNK-induced adenocarcinoma of the lungs and pancreas - Al-Wadei, Hussein A. N. (2009)
Small airway-derived pulmonary adenocarcinoma (PAC) and pancreatic ductal adenocarcinoma (PDAC) are among the most common human cancers and smoking is a risk factor for both. Emerging research has identified cAMP signaling stimulated by the stress neurotransmitters adrenaline and noradrenaline as important stimulators of several adenocarcinomas, including PAC and PDAC. The nicotine-derived nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) is a potent mutagen and the most powerful tobacco carcinogen. NNK is also an agonist for nicotinic acetylcholine receptors (nAChRs). Using hamster models of NNK-induced PAC and PDAC, we have tested the hypothesis that in analogy to chronic effects of nicotine in the brain, NNK may modulate the α(7)- and α(4)β(2)nAChRs, causing an increase in stress neurotransmitters and decrease in the inhibitory neurotransmitter γ-aminobutyric acid (GABA). In support of our hypothesis, immunoassays showed a significant increase in serum adrenaline/noradrenaline and increased intracellular cAMP in the cellular fraction of blood of NNK treated hamsters. Western blots were done with cells harvested by laser capture microcopy from control small airway epithelia, alveolar epithelia, pancreatic islet and pancreatic duct epithelia and from NNK-induced PACs and PDACs. The GABA synthesizing enzyme glutamate decarboxylase 65 (GAD65) and GABA were suppressed in NNK-induced PACs and PDACs whereas protein expression of the α(7)nAChR, α(4)nAChR as well as p-CREB and p-ERK1/2 were upregulated. These findings suggest, for the first time, that NNK-induced alterations in regulatory nAChRs may contribute to the development of smoking-associated PAC and PDAC by disturbing the balance between cancer stimulating and inhibiting neurotransmitters.